Tax factors influencing on tributation formality in restaurants from Santa Anita, Miraflores y San Isidro Districts at Lima - Peru - Uribe Hernández, Yrene (2015)
Establishes tax factors influencing directly on the formality of the service companies of restaurants in the districts of Santa Anita, Miraflores and San Isidro. The study was conducted during 2014, with a sample of 270 restaurants, 114 corresponding to Santa Anita, 72 to 84 to Miraflores and San Isidro. A survey validated using Cronbach's alpha was developed, frequencies were calculated and the influence was determined; among some of the factors studied on tax compliance it was determined by Xi2. Santa Anita showed a sample with highest values of central tendency and dispersion Miraflores and San Isidro; Miraflores showed the highest number ofcomponents of the company and Santa Anita showed a wider range of educational attainment. In the three districts there was agreement that influenced profitability taxation. In Miraflores and San Isidro there was agreement on the role that the SUNAT met, as well as working conditions and training of personnel. Finally all the factors analyzed statistically significantly influenced the fulfillment of tax obligations.